Authority of a Notary Related to Marriage Agreements After the Decision of the Constitutional Court Number 69/PUU-XIII/2015 - Ida Bagus Kade Wahyu Sudhyatmika; I Nyoman Bagiastra (University of Udayana, 2022)
The purpose of this study is to analyze the arrangements related to marriage agreements in Indonesia and examine the authority possessed by notary related to marriage agreements after the Constitutional Court Decision. This paper is a normative legal research method since the focus of the study departs from the vagueness of norms by using several approaches: statute approach, conceptual approach, and analytical approach. The results of the study indicated that arrangements related to marriage agreements are subject to the provisions of the Marriage Law and the Civil Code. Referring to the provisions in Article 29 of the Marriage Law, it is understood that at or before the marriage takes place both parties with mutual consent can enter into a written agreement ratified by the civil registration officer, after the contents also apply to third parties. Furthermore, there has been a change in the authority of the Notary after the Constitutional Court’s Decision, however, until now the Notary has not been able to ratify the marriage agreement as referred to in the Constitutional Court’s Decision. For that we need a new mechanism that can be regulated in implementing regulations related to the authority of a Notary to ratify a marriage agreement, which the result that the ratification of a marriage agreement made by anNotary can be accessed by the public and can provide legal certainty for the parties involved in the marriage agreement, including third parties and also notaries who ratify.